Pension Reform in India - Gillingham, Robert (IMF Working Papers; Working Paper ;, 2001)
This paper reviews the current state of the pension system in India, as well as plans to reform it. Problems with the current system are identified, and, within this context, the appropriate role of the government in retirement saving is discussed. Finally, the OASIS reform proposal is evaluated and additional reform options are presented.